Вихідці Сумщини – вихованці Києво-Могилянської академії - Мицик, Ю.А.; Тарасенко, І.Ю. (Сіверщина в історії України, 2021)
У статті наводяться дані про вихованців Києво-Могилянської академії –
уродженців Сумщини, тобто земель, які у XVII–XVIII ст. входили до
складу Ніжинського полку Гетьманщини, а також Слобожанщини. Вона
продовжує наше аналогічне дослідження стосовно Глухова і Глухівщини
ХVІІ–XVІІІ ст. Охарактеризовано систему навчання в Києво-Могилянській
академії, поділ її на вісім класів (чотири вищих, чотири нижчих), де повний
курс навчання тривав дванадцять років. Головним джерелом послужили
списки студентів 30–40-х років XVIII ст., які стосувалися переважно
дітей духовенства і були опубліковані на початку ХХ ст. істориком
М.І. Петровим. Встановлено вихідців з території майбутньої Сумщини,
які здобували освіту в Києво-Могилянській академії в різних її класах,
указано на причини незавершення багатьма студентами повного курсу
навчання, простежено в деяких випадках подальшу їх кар’єру. Указано
також на зміни прізвищ студентів, утворення їх від патронімів або їхнього
місця народження. Встановлено роль земель Сумщини у культурному,
церковному і політичному житті Гетьманщини. The article presents data on the pupils of the Kyiv-Mohyla Academy –
natives of Sumy region, lands that in the XVII–XVIII centuries were part of the
Nizhyn Regiment of the Hetmanate, as well as Slobozhanshchina. It continues
our similar study of Hlukhiv and Hlukhiv region of the seventeent – eighteenth
centuries. The article describes the system of education at the Kyiv-Mohyla
Academy, its division into eight classes (four higher, four lower), where the full
course of study lasted twelve years. The main source was the lists of students
of the 30s and 40s of the 18th century, which concerned mainly children of the
clergy and were published in the 20th century. historian M.I Petrov. The received
education was the first step in the further career for young people and even a
pass to another еstate. Graduates of the academy had the opportunity to choose
a further path either in the church (to become a priest, get a parish) or to get a
position, for example in the General Chancellery. The article identifies people
from the territory of the future Sumy region who studied at the Kyiv-Mohyla
Academy in its various classes, points out the reasons why many students did
not complete the full course of study, and in some cases traces their further
careers. The changes of students’ surnames, their formation from patronymics
or their place of birth are also indicated. The role of Sumy lands in the cultural,
ecclesiastical and political life of the Hetmanate was established.